Association between Self-Esteem, Self-Efficacy, Peers, Parental Controls and Sexual Behavior in Adolescentsat High School, Surakarta - Winarni -; Okid Parama Astirin; Ruben Dharmawan (Journal of Health Promotion and Behavior, 2016)
Background: Sexual behavior among teenagers is worrying. It is influenced of permissive attitude shift, causing violation of norms, ethics in society. One factor is the opening of information about sex freely circulating in the community. In Surakarta adolescent at high school never did kiss the lips of 10.53%, a kiss in 5.6%, 4.23% masturbation and sexual intercourse 3.09%. This study aimed to determine the association of self-esteem, self-efficacy, peers, parents, with premarital sexual behavior in adolescent high school in Surakarta.Subjects and Method: This was an observational analytic study with cross sectional design. A total sample of 113 respondents was taken by using proportional random sampling. The population was in ten high schools of 1663 subjects in Surakarta. Data analysis used linear regression.Results: There is a relationship of self-esteem with premarital sexual behavior (b1= -0.202; 95% CI= -0.39 to -0.01; p= 0.036) were significantly higher self-esteem then reduce premarital sexual behavior. There is a relationship of self-efficacy with premarital sexual behavior (b2= -0.168; 95% CI= -0.33 to -0.01; p= 0.041) were significantly higher self-efficacy students then reduce premarital sexual behavior. There are peer relationships with premarital sexual behavior (b3= -0.271; 95% CI= -0.51 to -0.04; p= 0.024) were significantly better peer support and will reduce premarital sexual behavior. There is a parental relationship with premarital sexual behavior (b4= -0.236; 95% CI= -0.44 to -0.03; p= 0.025), the better the more parental supervision reduce premarital sexual behavior. There is a relationship of self-esteem, self-efficacy, peers, parents with premarital sexual behavior (F = 10.053; 95% CI= 24.16 to 43.61; p <0.001; R 2 = 24.4%)Conclusion: Self-esteem, self-efficacy, peers, and parents are associated with premarital sexual behavior in adolescents of 24.4%. Seventy six point six percent is influenced by other variables outside the research model.Keywords: Self-esteem, Self Efficacy, Peers, Parents Supervision, Premarital sex behaviorCorrespondence: Winarni. School of Public Health, Sebelas Maret University, Surakarta.Journal of Health Promotion and Behavior (2016), 1(1): 46-53https://doi.org/10.26911/thejhpb.2016.01.01.07